Évaluation Comparative De La Qualité Nutritionnelle Et Sanitaire Du Lait De Différentes Races De Vaches De Quelques Zones D’élevage Du Bénin - Dossou, Joseph; Atchouké, G. Donald; Dabadé, D. Sylvain; Azokpota, Paulin; Montcho, Jules Karel (European Scientific Journal, ESJ, 2016)
In this study, a comparative assessment of the nutritional quality and the safety of milk from cow breeds Girolando, Borgou, Borgou-Gir, and Lagunaire produced in Benin was carried out in the public breeding centers of Kpinnou, Bétécoucou, Okparaand in private farms in Adjohoun, respectively. Milk from the breed Borgou-Gir had the highest concentrations of macronutrients (protein and lactose) and minerals (magnesium: 197.556 ± 0.001 ppm, calcium: 2056.32 ± 0.000 ppm, and zinc: 5.522 ± 0.000 ppm). Analyzed milk samples were free of tuberculosis and brucellosis germs, and no mastitis prevalence was detected in milking cows. However, some milk samples had lead levels exceeding the maximum limit of 0.02 ppm prescribed by the Codex Alimentarius standard. In addition, milk from the breeds Borgou and Borgou-Gir contained pesticide residue levels, namely chlorpyrifos (0.12 ± 0.020 ppm) and cypermethrin (0.03 ± 0.020 ppm) higher than the Codex Alimentarius standard (0.01 ppm). Milk samples from Adjohoun and Kpinnou had an aflatoxin M1 level of 0.3 ± 0.000 ppb and 0,010 ppb ± 0.24, respectively and were not in agreement with the Codex Alimentarius standard (0, 05 ppb). Although rich in nutrients, analyzed cow’s milk may present health risks to consumers due to chemical contaminants.